2019
DOI: 10.21203/rs.2.15732/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiology of intestinal parasitic infections in preschool and school-aged Ethiopian children: A systematic review and meta-analysis

Abstract: Background : Numerous studies have been carried out on assessing the prevalence of intestinal parasites infections (IPIs) among preschool and school age children in Ethiopia, however, there was no study to gather and systematically analyze this information for policy makers. Methods : We searched Medline via PubMed, Scopus, Science Direct, Web of Science (ISI), and Google Scholar and local peer-reviewed journals published from inception to 2019 for studies describing prevalence of IPIs among preschool and scho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 108 publications
(30 reference statements)
3
4
0
Order By: Relevance
“…This result is consistent with data reported by Chelkeba et al [18] and Daryani et al [20]. School‐age children have a higher morbidity burden associated with intestinal parasitism due to their habits of playing or handling contaminated soil, eating with dirty hands, drinking and eating contaminated food and poor hygiene practices [3, 18, 33, 36]. The WHO has estimated that more than 600 million school‐age children live in areas with intense transmission of geohelminths and need treatment and prevention interventions.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This result is consistent with data reported by Chelkeba et al [18] and Daryani et al [20]. School‐age children have a higher morbidity burden associated with intestinal parasitism due to their habits of playing or handling contaminated soil, eating with dirty hands, drinking and eating contaminated food and poor hygiene practices [3, 18, 33, 36]. The WHO has estimated that more than 600 million school‐age children live in areas with intense transmission of geohelminths and need treatment and prevention interventions.…”
Section: Discussionsupporting
confidence: 94%
“…The prevalence of IPIs in school‐age children was 66%, which was significantly higher than that in preschool‐age children (37%). This result is consistent with data reported by Chelkeba et al [18] and Daryani et al [20]. School‐age children have a higher morbidity burden associated with intestinal parasitism due to their habits of playing or handling contaminated soil, eating with dirty hands, drinking and eating contaminated food and poor hygiene practices [3, 18, 33, 36].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…e result showed that the trend of HIHPIs in Ethiopia was reduced. e outcome was similar to a systematic review, and meta-analysis was conducted in Ethiopia in which the pooled prevalence in the years 1997-2002, 2003-2008, 2009-2014, and >2014 was 71%, 42%, 48%, and 42%, respectively [115]. e potential reason for this decreasing rate might be due to the development of awareness about the transmission and prevention mechanisms of HIHPIs and mass deworming programs [116].…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, over 600 million school-aged children were vulnerable due to IPIs [7]. Present prevalence (40.5%) was lower than that of PSC in Ethiopia (52%) [13], Burkina Faso (60.8%) [14], Cote d'Ivoire (55.2%) [15], Nigeria (86.2%) [16], São Tomé and Príncipe (64.7%) [17], and Pakistan (52.8%) [18], while it was higher than that in Western Saudi Arabia (12%) [19], Iran (21.5%) [20], India (27.5%) [20], Nepal (31.5%) [21], Marshall Islands (22.8%) [22], and Senegal (35%) [23]. Te diference in prevalence can be attributed to the following reasons: the timing of the survey due to deworming schedule, environmental conditions of the target areas, or contamination of water supplies [24].…”
Section: Discussionmentioning
confidence: 99%